Analisis Pengaruh Good Corporate Governance (GCG) Terhadap Integritas Laporan Keuangan Dengan Kualitas Audit Sebagai Pemoderasi : Studi Pada Perusahaan Manufaktur Sub Sektor Industri Dasar dan Kimia Yang Terdaftar di BEI Periode 2019-2022 - Nur Halimah; Sri Yuni; Agus Kubertein (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to examine the influence of institutional ownership and independent commissioners on the integrity of financial reports with audit quality as a moderator. The population in this study are manufacturing companies in the basic industry and chemical sub-sectors listed on the IDX for the 2019-2022 period. The sampling method uses sampling with a total sample of 46 companies. The data analysis technique uses the SPSS version 25 program. The data analysis technique in this research uses descriptive statistics, classical assumption tests, multiple regression analysis, moderated regression analysis and hypothesis testing using the t test and coefficient of determination test. The test results show that institutional ownership has no effect on the integrity of financial reports, while independent commissioners have a negative and significant effect on the integrity of financial reports. Then audit quality as a moderator is unable to moderate the influence of institutional ownership on the integrity of financial reports. Meanwhile, audit quality is able to moderate the influence of independent commissioners on the integrity of financial reports